Synthesis, characterization and controlled release properties of zincaluminium-beta-naphthoxyacetate nanocomposite - Jubri Z.; Yusoff N.Z.A.M.; Sarijo S.H.; Marsom E.S.; Hussein M.Z. (Springer New York LLC, 2023)
Carbon; Characterization; Herbicides; Nanocomposites; Nanostructured materials; Precipitation (chemical); Weed control; Zinc; Beta-naphthoxyacetate; Controlled release formulations; Controlled release properties; Coprecipitation method; Deintercalation process; Hydrotalcites; Layered double hydroxides; Pseudo second order kinetics; Aluminum